2014
DOI: 10.1007/jhep09(2014)125
|View full text |Cite
|
Sign up to set email alerts
|

Precision unification and proton decay in F-theory GUTs with high scale supersymmetry

Abstract: F-theory GUTs provide a promising UV completion for models with approximate gauge coupling unification, such as the (non-supersymmetric) Standard Model. More specifically, if the superparters have masses well above the TeV scale, the resulting imperfection in unification can be accounted for by the, in principle calculable, classical F-theory correction at the high scale. In this paper we argue for the correct form of the F-theory corrections to unification, including KK mode loop effects. However, the price o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 147 publications
(281 reference statements)
0
14
0
Order By: Relevance
“…This along with the splitting between the masses of bino and other gauginos allow SUSY breaking scale to be raised all the way up to the GUT scale without causing instability in the electroweak vacuum or entering into the conflict with the observed Higgs mass. Our framework is, therefore, different from the standard split or high-scale SUSY scenarios, see for example [9,14,47], in which the supersymmetry breaking scale is restricted to appear at the intermediate scales.…”
Section: Conclusion and Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This along with the splitting between the masses of bino and other gauginos allow SUSY breaking scale to be raised all the way up to the GUT scale without causing instability in the electroweak vacuum or entering into the conflict with the observed Higgs mass. Our framework is, therefore, different from the standard split or high-scale SUSY scenarios, see for example [9,14,47], in which the supersymmetry breaking scale is restricted to appear at the intermediate scales.…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…(6) with matching conditions, Eqs. (9,10), at the gaugino mass scales. The decoupling of bino and wino from the spectrum also leads to threshold corrections in the quartic couplings at the respective scales.…”
Section: A Matching At M Smentioning
confidence: 99%
See 1 more Smart Citation
“…Such relations have been studied in the perturbative Type IIA framework in [15]. The need for the moduli to obey such relations might seem ad hoc to GUT model builders; on the other hand even in GUT realisations of string theory important corrections, in the example of F-theory due to hypercharge flux or Kaluza-Klein states [8,103,[146][147][148], render unification less non-trivial than one might think.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that in order for SUSY to be reconciled with the observed Higgs mass, there are constraints from the requirement that unification at the high scale still occur [3][4][5][6]. There are also experimental lower limits [7][8][9][10], and theoretical studies of upper limits on the scale of superpartners [4,[11][12][13][14][15][16][17][18][19][20][21]. However, for the most part, these studies have been concerned with determining approximate limits on the SUSY breaking scale in setups where the SUSY spectrum is close to degenerate.…”
Section: Introductionmentioning
confidence: 99%